IPTEKS PROSES PENYUSUNAN ANGGARAN SEKTOR PUBLIK PADA BADAN PERENCANAAN PEMBANGUNAN, PENELITIAN DAN PENGEMBANGAN DAERAH (BAPELITBANGDA) KOTA MANADO - Mentang, Fanda J.; Makaminang, Nitha E.; Saerang, David P.E. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
The Development Planning Agency, Regional Research and Development of the City of Manado is a body that assists the Mayor in supporting government affairs in the fields of planning, research and development. In each program and activity requires funds, to see good financial use, a good budgeting process is needed that is in accordance with the guidelines in legislation which can reduce the risk of ineffective use of the budget. The purpose of the study was the Bapelitbangda of Manado city to provide information on how the government adhered to every regulation and policy regarding budgeting to create an accountability public sector organization. In accordance with Minister of Home Affairs Regulation No. 33 of 2017 concerning budgeting guidelines where Bapelitbangda is quite effective in implementing every rule and policy of regional government in terms of budgeting.Keywords: public sector budgeting process, Bapelitbangda Manado City